Studi Perbandingan Penerapan Model Pembelajaran Two Stay Two Stray dan Jigsaw Ditinjau dari Hasil Belajar Matematika - Sibtil Hasaniah; Laila Hayati; Nani Kurniati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
This study was aimed to discover the comparison of the cooperative learning model betweenÃÂ two stay two stray type and jigsaw typeon thesubject of patterns and row of numbers in SMPN 1 Gunungsari academic year 2019/2020. This researchis considered as quasi experiment group design in whish post test was used. The sample was taken using cluster random sampling, students of VIII-A and VIII-C were used as the sampel. The instruments used in this research were written test and observation sheets consisting of learning process, teacher and studentÃ¢â¬â¢s activities.The studentsÃ¢â¬â¢ score in using the two sttay two stray class shows an average score 63,67 with 26.66% classical completeness. While in the jigsaw class,the average of studentsÃ¢â¬â¢ score was 65,33 with 30.00% classical completeness. Although the result of both classes are low, but both classes haveÃÂ increased learning activities each meeting. The implementation of the learning model has been carried out 97%. Furthermore, teacher activities were coresponded with the study plans. The result of this study shows that there is no significant differences betweenÃÂ two stay two stray typeandÃÂ jigsawÃÂ type in cooperative learning modelon thesubject of patterns and row of numbers in VIII grade SMPN 1 Gunungsari academic year 2019/2020.